Active independent directors and earnings quality - KUSNADI, Yuanto (Institutional Knowledge at Singapore Management University, 2022)
We examine the relationship between active independent directors and earnings quality for U.S. firms. We construct measures that proxy for activeness of independent directors and find that the proportion of active independent directors is under half on average. Our finding shows that earnings quality increases with the percentage of active independent directors on the board. Once the active independent directors are separated out, the other independent directors do not have any effect on earnings quality. This finding supports the hypothesis that the activeness of independent directors is incrementally significant over just the proportion of independent directors for the quality of reported earnings.